The study of paleometry in the Araripe Basin (Research, Society and Development, 2023)
The present research is a bibliographic review of the narrative type, with the objective of presenting the state of the art, containing an updated overview of all the published works referring to the use of paleometric techniques in the characterization of the fossils belonging to the Araripe Basin in a way chronological in time and space. The information was obtained through searches in online databases, in addition to queries in academic repositories. The use of paleometry began to expand in the scenario of this stratigraphic unit from the research by Lima and collaborators in 2007. Although 16 years have passed since these pioneering works, few studies have been published, totaling only 17 works so far, in addition to that these researches were restricted, almost exclusively to the Santana Group (in the Crato, Ipubi and Romualdo Formations), thus existing a gap for the other Formations that hold fossils, which make up the geological history of the region. It is hoped that the data gathered and presented here can subsidize and encourage future research in the area, thus contributing to the progress and expansion of paleometry in the Araripe Basin.